Contenidos sustantivos y metaconceptos históricos en narrativas de estudiantes de la carrera de educación primaria - Tapia Chávez, Ana María (Pontificia Universidad Católica del Perú., 2023)
This research aimed to describe how a group of student’s primary education career used substantive knowledge and meta-concepts in the elaboration of their historical narratives about the Peruvian Independence process. To do this, a qualitative methodology was used. For the analysis, the instrument of levels of complexity of the substantive knowledge and meta-concepts (Sáiz & Gómez, 2016) was used. Additionally, open coding was performed to identify emerging categories in student narratives. Most narratives showed low levels of complexity in the use of meta-concepts and substantive knowledge. It also identified the presence of several of the traits of master narratives.

Esta investigación tuvo como objetivo describir cómo un grupo de estudiantes de la carrera de educación primaria utiliza contenidos históricos sustantivos y metaconceptos históricos en la elaboración de sus narrativas históricas en relación con el proceso de la Independencia del Perú. Para ello, se utilizó principalmente una metodología cualitativa. Para el análisis se utilizó el instrumento de niveles de complejidad de los contenidos sustantivos y metaconceptos históricos (Sáiz y Gómez, 2016). Adicionalmente, se realizó una codificación abierta para identificar categorías emergentes. La mayor parte de las narrativas evidenciaron bajos niveles de complejidad el uso de metaconceptos históricos y contenidos sustantivos; así como rasgos de las denominadas narrativas maestras.
Substantive knowledges and Historical Metaconcepts in Narratives of Primary Education Career Students
Keywords: Substantive knowledge; Meta-concepts; Historical thinking; Historical narratives; Teaching history; Teacher education; Contenidos sustantivos; Metaconceptos históricos; Pensamiento histórico; Didáctica de la historia; Formación docente; https://purl.org/pe-repo/ocde/ford#5.03.00